Analisis Deiksis Dalam Unggahan Akun 《常高俊April》 di Media Sosial Weibo (微博): Kajian Pragmatik - Rika Laudina; Vivi Adryani Nasution (PT FORMOSA CENDEKIA GLOBAL, 2022)
常高俊April is one of the information dissemination accounts that contains a lot of deixis on Weibo. With the different contexts and situations of the author and reader, the meaning of deixis is also different. This study aims to find out the types and the meaning of deixis contained in 常高俊April account uploads. This study used qualitative descriptive methods with data in the form of words contained in 常高俊April account uploads. The results of this study showed that there are five types of deixis in 常高俊April account uploads, namely persona deixis, place deixis, time deixis, social deixis and discourse deixis. In addition, this study shows that the meaning of words whose references change can be known by paying attention to the context of speech.